DEVELOPMENT OF E-DESA POLICY MODEL IN BANDUNG REGENCY (EDUCATION QUALIFICATION TECHNOLOGY OF PERANGKAT DESA) - Purnawingwulan, dkk, Melly Maulin (Prodi Teknologi Pendidikan, 2015)
Abstract. Electronic Desa (e-Desa) is a system that based on cloud computing technology, then the government shouldn't bothered by infrastructure suplly such as server, aplication, and system tendance. The hope with the introduction of this e- Desa system are village government is able to self-financed in the information management and administrative conducted. The aims of developing e-Desa are specificly for getting a management information model and administrative conducted by village government to increase service in apropriate with vission and mission Bandung Regency in regional autonomy spirit. This research has for giving basic contribution in government science esspecially to new concept about e-Government. This research used description method with qualitative approach then the determination technique of informants using purposive (taking informants based on the aims). Collecting data technique that used in this research is library studies and range studies long data validity in this research using triangulation. Result of the research showed that development of e-Desa policy model can be successful if it's supported by adequate technology educational qualifications of the village government. In fact, there was still lacking in the village government of bandung district government environment.Keywords: Policy, e-Desa, e-Government.Abstrak. Electronic Desa (e-Desa) merupakan sistem yang dapat didasarkan pada teknologi cloud computing. Dengan e-Desa maka pemerintah desa tidak perlu direpotkan dengan penyediaan infrastruktur sistem seperti server, aplikasi dan perawatan sistem. Harapan dengan adanya sistem e-Desa ini adalah pemerintah desa dapat mandiri dalam pengelolaan informasi dan administrasi yang dilakukan. Pembangunan e-Desa ini ditujukan khusus untuk mendapatkan model pengelolaan informasi dan administrasi yang dilakukan pemerintahan desa guna meningkatkan pelayanan sesuai dengan visi dan misi Kabupaten Bandung dalam semangat otonomi daerah. Penelitian ini memiliki tujuan untuk memberikan kontribusi mendasar pada Ilmu Pemerintahan khususnya tentang konsep baru tentang e-Government. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif dengan teknik penentuan informan yang digunakan purposive (pengambilan informan berdasarkan tujuan). Teknik pengumpulan data yang digunakan dalam penelitian ini adalah studi pustaka dan studi lapangan serta validitas data dalam penelitian ini menggunakan triangulasi. Hasil penelitian menunjukkan bahwa pengembangan model kebijakan pembangunan e-Desa dapat berhasil bilamana ditunjang oleh kualifikasi pendidikan teknologi perangkat desa yang memadai. Kenyatannya, hal ini masih kurang di kalangan perangkat desa di lingkungan Pemerintah Kabupaten Bandung.Kata Kunci : Kebijakan, E-desa, E goverment